Ecolinguistics as a New Field of Linguistics (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In this article, the first comments on the ecological issues of language were presented. The research sources of the linguistic ecology of the Uzbek language were talked about. There was talk about the factors that preserve the purity of the language. The factors that determine the development of the language were also discussed.